Does the level of inferior mesenteric artery ligation affect short-term and long-term outcomes of patients with sigmoid colon cancer or rectal cancer? A single-center retrospective study - Yawei Wang; Yan Wang; Liaonan Zou; Lingna Deng; Tianchong Wu; Linsen Liu; Jiling Jiang; Tailai An (World Journal of Surgical Oncology, 2022)
Abstract Background For sigmoid colon or rectal cancer, a definite consensus regarding the optimal level ligating the inferior mesenteric artery (IMA) has not been reached. We performed this study to determine whether the ligation level significantly affected short-term and long-term outcomes of patients with sigmoid colon or rectal cancer after curative laparoscopic surgery. Methods Medical records of patients with sigmoid colon or rectal cancer who had undergone curative laparoscopic surgery between January 2008 and December 2014 at the Department of Gastrointestinal Surgery, Guangdong Provincial Hospital of Traditional Chinese Medicine were reviewed. Then, the high tie group (HTG) was compared with the low tie group (LTG) in terms of short-term and long-term outcomes. Results Five-hundred ninety patients were included. No significant differences between two groups regarding baseline characteristics existed. HTG had a significantly higher risk of anastomotic fistula than LTG (21/283 vs 11/307, P = 0.040). Additionally, high ligation was proven by multivariate logistic regression analysis to be an independent factor for anastomotic fistula (P = 0.038, OR = 2.232, 95% CI: 1.047–4.758). Furthermore, LT resulted in better preserved urinary function. However, LTG was not significantly different from HTG regarding operative time (P = 0.075), blood transfusion (P = 1.000), estimated blood loss (P = 0.239), 30-day mortality (P = 1.000), ICU stay (P = 0.674), postoperative hospital stay (days) (P = 0.636), bowel obstruction (P = 0.659), ileus (P = 0.637), surgical site infection (SSI) (P = 0.121), number of retrieved lymph nodes (P = 0.501), and number of metastatic lymph nodes (P = 0.131). Subsequently, it was revealed that level of IMA ligation did not significantly influence overall survival (OS) (P = 0.474) and relapse-free survival (RFS) (P = 0.722). Additionally, it was revealed that ligation level did not significantly affect OS (P = 0.460) and RFS (P = 0.979) of patients with stage 1 cancer, which was also observed among patients with stage 2 or stage 3 cancer. Ultimately, ligation level was not an independent predictive factor for either OS or RFS. Conclusions HT resulted in a significantly higher incidence of anastomotic fistula and worse preservation of urinary function. Level of IMA ligation did not significantly affect long-term outcomes of patients with sigmoid colon or rectal cancer after curative laparoscopic surgery.